Segurança do paciente na compreensão dos estudantes de graduação da área da saúde - Cauduro, Graziela Maria Rosa (2016)
The present study aimed to assess the knowledge of undergraduate students in the healthcare area regarding patient safety. This is a cross-sectional descriptive study, conducted with 638 undergraduate students from the areas of nursing, medicine, odontology, physiotherapy, speech therapy, pharmacy and occupational therapy of the Federal University of Santa Maria, RS, Brazil. The data collection occurred from March until June 2015, by means of an online questionnaire with questions referring to students characterization, as well as aspects concerning concepts and attitudes on human error and patient safety. The data were collected after being approved by the Commitee of Ethics in Research of the Federal Unviersity of Santa Maria (CEP/UFSM), under the CAAE n. 40248714.4.0000.5346. The database was organized in a spreadsheet using Excel® and later it was analyzed by the Predictive Analytics SoftWare®, by means of descriptive statistics. The results presented a predominance of female students (77,7%), aged between 18 and 22 years old (56,1%), mostly attending the third, fifth and seventh terms and residents to neighboring areas to the university. The finding as regards scholarship discovered 57,4% of the students did not have any sort of scholarship. Among the students who received a scholarship, the predominance of permanence scholarships (42,6%) and scientific initiation scholarshipes (31,3%) was identified. Most students declared not having any formal classes on the issue, but some evidences were found which indicate conceptions regarding human error and patient safety that appear in accordance with the principles guiding the National Program of Patient Safety. We believe that the results of this study may contribute to the reflections over the challenges for the academic formation and aid in the creation of a specific course and in the importance of the cross-sectionality of the issue in different levels of education.